Path-loss modelling for WSN deployment in indoor and outdoor environments for medical applications - Bashar Fakhri, Ahmed; Kamel Gharghan, Sadik; Latteef Mohammed, Saleem (International Journal of Engineering and Technology, 2018)
Wireless sensor networks (WSNs) and their applications have received significantly interested in the last few years. In WSN, knowing an accurate path-loss model as well as packet delivery should be taken into account for the successful distribution of several nodes in the net-work. This paper presents a path-loss modeling and performance evaluation of the ZigBee wireless standard. Received signal strength indi-cator (RSSI) measurements were achieved in outdoor and indoor environments to derive the path-loss based on Log-Normal Shadowing Model (LNSM). The path-loss parameters such as standard deviation and path loss exponents were estimated over point-to-point ZigBee WSN. In addition, the variances of received RSSI values and standard deviation for these values have been investigated. Furthermore, the data packets received is measured practically. Results revealed that the LNSM can be estimated to reflect the channel losses in both outdoor and indoor environments for medical application. The data delivery was achieved successfully of 100% in outdoor which better than indoor due to multipath propagation and shadowing. Moreover, the data packets delivery of the current work outperformed previous work.Â Â